2018
DOI: 10.1017/gmh.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

“I feel that life is meaningless”: Vietnamese adolescents' experiences of and reflections about interpersonal violence

Abstract: BackgroundThe experiences of and reflections on interpersonal violence and victimisation among adolescents living in low- and middle-income countries are poorly understood. The aim was to describe Vietnamese adolescents’ reflections on their experiences of victimisation.MethodA self-completed, cross-sectional survey investigating exposure to violence among high school students in Hanoi, Vietnam was conducted during 2013–2014. The last section invited participants to write about any of the matters covered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These longitudinal and several cross-sectional (Meyer et al ., 2017; Bajunirwe et al ., 2018; Malan et al ., 2018; Rees et al ., 2018) and qualitative studies (Le et al ., 2018) in the series confirm the negative impacts from various types of interpersonal violence on a range of mental health outcomes, including suicidality.…”
Section: Interpersonal Violence and Mental Health: Overview Of The Sementioning
confidence: 73%
“…These longitudinal and several cross-sectional (Meyer et al ., 2017; Bajunirwe et al ., 2018; Malan et al ., 2018; Rees et al ., 2018) and qualitative studies (Le et al ., 2018) in the series confirm the negative impacts from various types of interpersonal violence on a range of mental health outcomes, including suicidality.…”
Section: Interpersonal Violence and Mental Health: Overview Of The Sementioning
confidence: 73%
“…In other words, the study demonstrated that, in the cultural context of Southeast Asia, the bond between children and parents/caregivers in the caring manner can help protect adolescents’ psychological health ( Nguyen et al, 2019 ). Likewise, a survey of high school students in Vietnam shows that poor communication between parents and adolescents has a negative impact on children’s mental health ( Le et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrates the utility and feasibility of analyzing open‐ended free‐text survey responses in patient outcomes research. Such questions are infrequently analyzed but can easily be added to study protocols and allow survivors to share the issues most important to them 20,32,33 …”
Section: Discussionmentioning
confidence: 99%